The Bet of Halala's Luck The Game of Time in Atai Nahay's Novel - Ali, Srwa Tahir; Meera, Ahmad Mohammed Rashid; Ali, Aram Omer; HamaFaraj, Dilan Salam; Abdulla, Kanyaw Bakr; Ma'roof, Sana Siddiq; Abdulqadir, Maudwd Jabar; Salih, Lava Othman (Journal of Linguistics and Social Sciences, 2024)
This study entitled (The Game of Time in Atai Nahai's Novel (The Bet of Halala's Luck) in which the genre of time is the center of the study. At the same time, the concept of time, and time as a prominent and influential genre of the novel, and then the relationship between time and the novel, has a great impact on the novel, to the extent that the author can not give up time in writing the novel. The presentation of techniques that lead to playing with parts of time creates a kind of breakdown in time, which creates aesthetics in the novel text that attracts the reader's attention. The study followed the descriptive analytical approach, and the necessary examples are presented for this purpose.